The clinical supervision experiences of nursing students: The good, the bad, and the ugly of nursing professionalism - Donough, G. (South African Journal of Higher Education, 2025)
Background: Clinical supervision is essential to nursing students’ transformation into skilled professional nurses in the healthcare field. Effective communication, emotional intelligence, cultural sensitivity, collaboration, and conflict resolution are some of the skills that professionals need to demonstrate as part of professionalism. The key environment for student nurses’ growth and development into competent professionals is the clinical learning environment, where they receive their training and gain practical experience. Aim: This study aims to explore nursing students’ clinical supervision experiences. Setting: At a nursing school in South Africa. Methods: Employing a qualitative descriptive design and obtaining ethical clearance, the study utilised focus group interviews guided by a semi-structured interview guide. A purposive sampling strategy was employed, resulting in 36 participants, with nine students per focus group, representing various educational levels over four years. Content analysis was applied for data interpretation. Results: The exploration of nursing students’ clinical supervision experiences revealed a central theme of professionalism. The study identified good aspects, including the demonstration of knowledge and positive reinforcement; bad aspects such as poor time management; and ugly aspects like unskilled and incompetent supervisors and abusive behaviour. Conclusion: Professionalism is a fundamental aspect of nursing education, significantly influencing student nurses’ training, particularly in the clinical learning environment. As students observe and emulate professional behaviours, the role of professionalism becomes crucial during expert guidance and professional assessments, facilitating their journey towards competency and proficiency. Contribution: This study enhances our understanding of how professionalism impacts student nurses’ development and learning outcomes in both clinical and theoretical teaching components. It contributes valuable insights to the evidence base of nursing education in practice.